Achieving high performance in silicone rubber dielectric elastomers via synergistic layer system - Ahmad Farimin, Ahmad Osman; Chan, Kah Yoong; Shamsul, Zakaria (Multimedia University, 2025)
Polydimethylsiloxane (PDMS) elastomers are attractive for soft actuation but their intrinsically low permittivity demands high electric fields and promotes premature electrical failure. To address this limitation, this study implements a Synergistic Layer System (SLS) in which a hard filler (TiO2) and soft fillers (high-permittivity silicone oil (HPSO) and glycerol (Gly)) are co-embedded in PDMS to raise dielectric response while moderating stiffness. A commercial PDMS A/B (1:1) pre-blend was formulated as single-filler films (TiO2, HPSO, Gly; 15 wt%) and SLS hybrids (TiO2 + Gly and TiO2 + HPSO; 1:1, total 15 wt%), then degassed, cast in glass Petri dishes, and oven-cured at 80 °C (~ 40–80 µm). Mechanical properties (Young’s modulus, tensile strength, elongation at break) were obtained by quasi-static uniaxial tensile testing on a universal testing machine. Breakdown strength followed IEC 60243-1/-2 using a step-up high-voltage setup with semi-spherical electrodes. Relative permittivity (Er) was measured on an impedance analyzer (20 Hz – 30 MHz) using carbon-grease circular electrodes. Relative to pure PDMS, single-filler films improved either dielectric response or compliance but introduced clear trade-offs. In contrast, the SLS hybrids delivered balanced gains- TiO2 + Gly increased Er while tempering stiffness and TiO2 + HPSO provided the most balanced combination of Er, modulus, and breakdown strength. These results show that co-embedding a hard filler with a soft filler in a single layer complements interfacial polarization and plasticization, enabling higher-performance PDMS actuators without excessive stiffness.